Deficits in tasks of executive functioning that mimic real-life scenarios in bipolar disorder - Torralva, Teresa (2012)
Background: A growing body of evidence suggests that patients with bipolar disorder (BD) have cognitive impairments even during euthymic periods. The main cognitive domains affected are verbal memory, attention, and executive function. Nevertheless, some studies suggest that at least a subgroup of euthymic patients demonstrates intact executive functioning in classic neuropsychological tests, which could be due to the lack of real-life, or ecological validity. Objective: In this study, we highlight the usefulness of incorporating more ecological tests of executive function in assessment batteries in order to detect specific cognitive deficits in BD patients with otherwise normal performance in standard executive tests. Methods: Nineteen euthymic BD patients and 15 healthy controls completed a standard neuropsychological battery assessment and two experimental tasks (the Multiple Errands Test-Hospital Version and the Hotel Task) to measure executive functioning in highly demanding cognitive settings that mimic real-life scenarios. Results: No significant differences were found between the groups' demographic variables. We found, as predicted, that the group of euthymic BD patients who had control-comparable performance in classic executive tasks showed important deficits in more ecological tasks of executive functioning of the type that mimic real-life scenarios. Conclusions: Together, these data suggest that the inclusion of ecological tests in the assessment of BD patients can contribute to providing a more realistic cognitive profile of this patient population, which will undoubtedly allow for a better design of therapeutic and rehabilitation strategies that can help patients to minimize impact in real-life settings.